2009
DOI: 10.1111/j.1365-2427.2008.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture, non‐native salmonid invasions and associated declines of native fishes in Northern Patagonian lakes

Abstract: 1. Even though intensive aquaculture production of salmonids in lakes occurs in many locations around the world published studies on the survival and reproductive success of escaped cultured salmonids in freshwater ecosystems are not common. A recent expansion of aquaculture in Chile has led it to become the world's second largest producer of cultured salmonids. 2. We document the recent history of escaped and self-sustaining salmonid populations over a wide spatial scale and a long temporal scale in Chilean P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 43 publications
4
125
2
6
Order By: Relevance
“…Una situación totalmente inversa a la propuesta por ambos autores, sucedería en la Patagonia de Argentina, donde en condiciones de oligotrofia existiría baja actividad zooplanctónica (Balseiro et al 2001, Modenutti et al 2003, lo cual sería similar a lo observado en los grandes lagos estudiados en el presente trabajo (Tabla 1, Fig. 2b) Un factor importante, en grandes lagos de la Patagonia es el efecto de la presencia de salmónidos asilvestrados (Soto et al 1994, Becker et al 2007, Pascual et al 2007, Arismendi et al 2009). Aunque en el presente estudio no se cuantificaron sus poblaciones, y no está demostrado un efecto potencial directo o indirecto de estas poblaciones de peces sobre zooplancton en lagos chilenos, es muy probable en sitios con poblaciones de salmónidos existan especies zooplanctónicas de menor tamaño corporal (Soto et al 1994), por desaparición de grupos de gran tamaño como cladóceros y copépodos (Modenutti et al 1998, Reissig et al 2006.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Una situación totalmente inversa a la propuesta por ambos autores, sucedería en la Patagonia de Argentina, donde en condiciones de oligotrofia existiría baja actividad zooplanctónica (Balseiro et al 2001, Modenutti et al 2003, lo cual sería similar a lo observado en los grandes lagos estudiados en el presente trabajo (Tabla 1, Fig. 2b) Un factor importante, en grandes lagos de la Patagonia es el efecto de la presencia de salmónidos asilvestrados (Soto et al 1994, Becker et al 2007, Pascual et al 2007, Arismendi et al 2009). Aunque en el presente estudio no se cuantificaron sus poblaciones, y no está demostrado un efecto potencial directo o indirecto de estas poblaciones de peces sobre zooplancton en lagos chilenos, es muy probable en sitios con poblaciones de salmónidos existan especies zooplanctónicas de menor tamaño corporal (Soto et al 1994), por desaparición de grupos de gran tamaño como cladóceros y copépodos (Modenutti et al 1998, Reissig et al 2006.…”
Section: Resultados Y Discusiónunclassified
“…Aunque en el presente estudio no se cuantificaron sus poblaciones, y no está demostrado un efecto potencial directo o indirecto de estas poblaciones de peces sobre zooplancton en lagos chilenos, es muy probable en sitios con poblaciones de salmónidos existan especies zooplanctónicas de menor tamaño corporal (Soto et al 1994), por desaparición de grupos de gran tamaño como cladóceros y copépodos (Modenutti et al 1998, Reissig et al 2006. De igual modo existiría una serie de interacciones del tipo efecto cascada, donde los salmónidos podrían depredar sobre peces nativos o compartir sus nichos tróficos , Arismendi et al 2009), lo cual no está del todo claro en cuanto a sus efectos sobre el zooplancton. Una situación diferente sucedería en presencia de peces nativos como puyes (Galaxias sp.…”
Section: Resultados Y Discusiónunclassified
“…The strong spatial segregation between P. trucha and rainbow trout intensified in Alicurá reservoir following the onset of aquaculture 25 years ago, also characterized by the almost total absence of O. hatcheri in littoral captures . This outcome may be a consequence of negative interactions taking place between the native fish and farm escapees, as has been argued for Chilean lakes (Arismendi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in Norwegian sea fjords reported numerous indigestible items in ERT stomach contents with less than a year in the wild, but not farm pellets or wild food (Rikardsen and Sandring, 2006;Skilbrei, 2012). Wild food and farm pellets, but not indigestible items, were found in ERT with probably more than a year since escape time in Chilean sea fjords (Soto et al, 2001) and lakes (Arismendi et al, 2009). In a semi-enclosed estuarine habitat in Tasmania, ERT consumed mainly farm pellets and indigestible items, but also small amounts of wild food, depending on time since escape (Abrantes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation